The Impact of Air Power : National Security and World Politics - Emme, Eugene M. (Lahore National Book Foundation, 1972)
"In many ways a pioneering work comparable to Admiral Mahan's classic study of sea power, this comprehensive volume gathers together the best that has been written or said about air and space power. It explores the full meaning and influence of air power upon national security and world politics. Major General Orvil A. Anderson, USAF (Ret.), Executive Director of the Air Force Historical Foundation and former Commandant of the Air West College, says, 'We have waited a long time for a book such as The Impact of Air Power."--Jacket.
Include Maps and Index
Keywords: Air power -- Military Policy